Effects of dexmedetomidine versus remifentanil on mothers and neonates during cesarean section under general anesthesia - Yu, Zhiqiang; Zhang, Peijun; Wang, Haiyun; Zhang, Li; Wei, Wei; Fang, Wenqian; Mu, Xingbo (Biomedical papers, 2020)
Background and Aims: Dexmedetomidine and remifentanil use in obstetric general anesthesia is controversial. This study aimed to compare the effects of remifentanil and dexmedetomidine on mothers and neonates during cesarean section under general anesthesia. Methods: A total of 120 patients scheduled for elective cesarean section under general anesthesia were randomly allocated to dexmedetomidine (D), remifentanil (R), and control (C) groups. Anesthesia was induced with propofol and muscle relaxants in all groups. Anesthesia in groups D and R was induced with dexmedetomidine (induction, 0.5 ug/kg; maintenance, 0.5 ug/kg.h) and remifentanil (induction, 0.5 ug/kg; maintenance, 2 ug/kg.h), respectively, until birth. Group C received equivalent volumes of normal saline. Mean arterial blood pressure (MAP), heart rate (HR), plasma catecholamine, visual analog pain score (VAS), and total tramadol consumption at 1, 2, and 3 hours after extubation were recorded. Neonatal effects were assessed by Apgar scores and umbilical blood gas analysis. Results: Post induction, MAP was significantly higher in group D compared to groups C and R, and significantly lower in group R than in group C. At intubation/skin incision and delivery, MAP, HR, and plasma epinephrine and norepinephrine concentrations were significantly lower in groups D and R than in group C. Compared to group R, MAP was significantly higher, and HR, plasma epinephrine, and norepinephrine concentrations were significantly lower in group D. Compared with groups C and D, the percentage of neonates with Apgar score < 7 was higher in group R at 1 min after delivery. Compared with groups C and R, the VAS was significantly lower in group D at 1 and 2 h postoperatively. Total tramadol consumption was significantly lower in group D at 3 hours postoperatively. Conclusion: During general anesthesia for cesarean section, remifentanil demonstrated better control of hemodynamic stability, while dexmedetomidine demonstrated better neonatal Apgar scores, postoperative analgesia, and decreased catecholamine release. Trial Registration: Chinese Clinical Trial Register (ChiCTR) - ChiCTR1800017125
Keywords: general anesthesia; cesarean section; remifentanil; dexmedetomidine